Լեռնային Ղարաբաղի Հանրապետության տարածքում հայտնաբերված ժանգասնկերի կարգաբանական վերլուծությունը - Մարգարյան, Գ․
Aнализ130 видов ржавчинных грибов в 10 родах и 6 семействах, выявленных в НКР показал, что по числу превосходит семейство Pucciniaceae. Идентифицировано 3 рода и 109 видов, принадлежащих к данному семейству. По распространенности, 2 место занял род Uromyces /численность 20 видов/. Крайне редки анаморфные виды: всего 3 вида. Из ржавчинных грибов, выявленных в НКР – 44 вида идентифицированы впервые. Большая их часть распространена по территории республики. The analysis of 130 species of rusts in 10 genera and 6 families in the NKR revealed that the most numerousis is the Pucciniaceae.There were identified 3 genera and 109 species belonging to this family. On the distribution, the 2nd place is taken by the Uromyces /20 species/. Anamorphs are extremely rare: only 3 species. Among the rusts revealed in NKR, 44 were identified for the first time. Their most part is widespread on the whole territory of the republic.
Keywords: Սնկաբանություն